OLERIKULTUR URBAN: Kontribusi untuk Meningkatkan Produksi Pangan Nabati untuk Masyarakat Perkotaan - Benyamin Lakitan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Lakitan B. 2021. URBAN OLERICULTURE: Contribution to increase vegetable production for urban community. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 1-10. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Population increase directly affects food demand. Since the increase will be concentrated in urban area, this trend should be appropriately responded by intensifying urban agriculture activities. Urban agriculture characterized with limited availability of agricultural land but better infrastructure than rural area. Urban dwellers are also more prepared to adopt advanced agricultural technology and have better access to financial sources. Technology-wise, hydroponics and vertical agriculture have been practiced by urban farmers. Besides for food production, urban agriculture gives other benefits, including aesthetics and better quality of local environment. In major city, green wall and green roof have been developed at tall buildings. Vegetables and ornamental plants are the most commonly used in urban area. In some developed countries, indoor vegetable cultivation has been practiced using artificial lightings and large scale plant factories had employed automation system using artificial intelligence technology. Regardless of rapid development on agricultural technology, the selected technology for local application should consider availability of local natural resources and financial capacity of native farmers. Intensification of urban and peri-urban agricultural activities is not expected to fully meet total urban food demand. Therefore, conventional agriculture in rural area is still strongly needed.